Endovascular treatment of intracranial vertebrobasilar artery dissecting aneurysms: Parent artery occlusion versus flow diverter. Issue 99 (February 2018) - Fang, Yi-Bin; Lin, Amy; Kostynskyy, Alex; Agid, Ronit; Tymianski, Mike; Radovanovic, Ivan; Krings, Timo; Pereira, Vitor Mendes
Abstract: Purpose: To compare the safety and efficacy of endovascular parent artery occlusion (PAO) and flow diverter (FD) treatment in treating vertebrobasilar dissecting aneurysms (VBDAs). Methods: A review of a prospective aneurysm database at our institution was performed to identify all consecutive patients with intracranial VBDAs managed with endovascular treatment, which were either PAO or FD. Clinical and imaging findings were compared between the two groups. Results: A total of 25 consecutive patients with 27 VBDAs were included. Seventeen VBDAs were treated by PAO, and 11 VBDAs were treated with FDs. Immediate total occlusion rate after initial treatment was higher in the PAO group than in the FD group (62.5% v.s. 9.1%, p = .018). Complete occlusion on follow-up at 18 months was more frequently observed in the PAO group (81.8%) compared to the FD group (55.6%), although the difference was not statistically significant (p = .433). Procedure related complication rate and mortality for the whole case series was 28% and 24% respectively, and were comparable in the two groups. Excellent outcome at discharge was achieved in 77.8% and 40% of patients treated with FD and PAO respectively, which was not statistically significant (p = .169). Excellent outcome at followed-up was comparable as well. Conclusions: PAO and FD treatment are both feasible options for treatment of VBDAs. PAO provide higher immediate complete occlusion rate compared to FD. Despite low initial complete occlusion rates, FD group presented a comparable long-term outcome and similar perioperative events rate compared to the PAO group.